I hate everyone--starting with me - Rivers, Joan (Berkley Hardcover, 2012)
"Joan Rivers, comedienne, actress, jewelry monger, lives by the golden rule: Do unto others before they do unto you--and for God's sakes, do it funny! During the past two hundred years Joan has gained acclaim as an award-winning entertainment goddess. Joan is an international star (she can sneer in eight different languages) having performed all over the world, raising eyebrows, dropping names, and getting laughs. Her career in comedy began with a fantastic sense of self-loathing, but, after spending a couple of years looking at the human decrepitude around her, she figured, "Why stop here when there are so many other things to hate?" Here--uncensored and totally uninhibited--Joan says "F.U. to P.C." and says exactly what's on her mind...And HER mind is a terrible thing to waste."--